Efeito dos carotenoides do urucum sobre a fragilidade eritrocitária in vitro e ex vivo - Beni, Anissa Algara (2019)
Erythrocytes are the cells with the main function of transporting respiratory gases to tissues. These cells exhibit high susceptibility to hemolysis in various pathologies due to oxidation of their cellular components. Under physiological conditions, the production of reactive oxygen species (ROS) is controlled by the endogenous antioxidant system, continuously maintaining balance. However, an overproduction of ROS results in an imbalance between the pro and antioxidant system, called oxidative stress. The carotenoids bixin (BIX) and norbixin (NBIX) are mainly found in annatto seeds (Bixa orellana L.). These compounds have excellent antioxidant capacity and anti-inflammatory action. The aim of this study was to evaluate the antioxidant activity and the ability of BIX and NBIX to protect erythrocytes from in vitro and ex vivo induced hemolysis. Healthy adults of both sexes participated in the study. Erythrocytes from 4 volunteers were isolated for the in vitro experiment and co-incubated with different concentrations of bixin or norbixin and three different inducers of cell fragility. In the ex vivo study, 8 volunteers received a daily capsule containing BIX or NBIX (0.5 mg/kg/day) or placebo for 7 days, in a crossover design. The randomized, double-blind, placebo-controlled clinical trial was performed using a 21-day washout period between treatments, so that all volunteers received all treatments at different times. After the last day of each treatment, blood was collected. Erythrocytes were isolated and incubated with three different cell damage inducers (2,2'-azobis (2-amidinopropane) dihydrochloride (AAPH), glucose and NaNO2), which act by different mechanisms. In both the ex vivo and in vitro studies, after incubation with the inducers, the erythrocytes were submitted to osmotic fragility tests, where the erythrocytes were exposed to different NaCl concentrations (0.2 to 0.9%), with erythrocyte resistance being evaluated later. Moreover, in the ex vivo experiment, the activity of catalase, superoxide dismutase and glutathione peroxidase, as well as the levels of lipid oxidation malondialdehyde (MDA) were evaluated. In vitro, BIX and NBIX not only reduced AAPH, glucose or NaNO2-induced erythrocyte membrane fragility, but also improved basal osmotic resistance in the micromolar range. BIX and NBIX supplementation significantly increased erythrocyte membrane resistance, and BIX supplementation was the most effective. In addition, BIX and NBIX protected erythrocytes from lipid peroxidation and improved the cellular redox environment. Our study demonstrates the antihemolytic potential of annatto carotenoids by preventing and/or reducing membrane fragility of human erythrocytes. Additionally, it contributes to broaden understanding of the beneficial properties of human consumption of carotenoids, especially BIX and NBIX.